Pengaruh Current Ratio, Debt to Equity Ratio dan Earning per Share Ratio terhadap Harga Saham pada Perusahaan Teknologi yang Terdaftar di Bursa Efek Indonesia - Ferdila; Ita Mustika (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2022)
Investing in stocks is an investment option that provides high returns in a relatively short time because stock prices are always fluctuating. This study aims to analyze the effect of Current Ratio, Debt To Equity Ratio and Earning Per Share Ratio on stock prices in technology companies listed on the Indonesia Stock Exchange. This research method uses quantitative time series data, data obtained from the IDX for three years from 2018-2020. Data processing was tested statistically through classical assumptions, multiple regression analysis and hypothesis testing with T test, F test and determination test. The results of the study partially current ratio has a positive and significant effect on stock prices, debt to equity ratio has no effect on stock prices and earnings per share ratio has a positive and significant effect on stock prices. Simultaneously prove that the current ratio, debt to equity ratio and earnings per share have a positive and significant effect on stock prices.